Necroimages: A Theoretical Approach to Political Representation in Contemporary Visual Culture - Bullón Gil, Coral (Eikón / Imago, 2021)
This paper analyzes the issues surrounding the others’ representations in today’s visual culture related to the situations of displacement and forced migration in the Mediterranean Sea and the value given to images of social crisis Attention is paid both to images that are part of the contemporary media flow, specifically viral images and their circulation through networks, and to Western activist art practices. The concept of “necroimages” is proposed in order to understand the relationships that make it possible to see and not see certain images, who the subjects are represented in them and what role they play. When analysing the selected case studies, we ask ourselves to what extent the use of this type of images is appropriate for the representation of non-hegemonic subjects and how effective their visualisation can be for raising awareness and for the political demands that are pursued from the same artistic works and discourses.